Gnawing Between Cells and Cells in the Immune System: Friend or Foe? A Review of Trogocytosis - Zhao, Siyu; Zhang, Lichao; Xiang, Suoyu; Hu, Yunyi; Wu, Zhongdao; Shen, Jia (Frontiers in Immunology, 2022)
Trogocytosis occurs when one cell contacts and quickly nibbles another cell and is characterized by contact between living cells and rapid transfer of membrane fragments with functional integrity. Many immune cells are involved in this process, such as T cells, B cells, NK cells, APCs. The transferred membrane molecules including MHC molecules, costimulatory molecules, receptors, antigens, etc. An increasing number of studies have shown that trogocytosis plays an important role in the immune system and the occurrence of relevant diseases. Thus, whether trogocytosis is a friend or foe of the immune system is puzzling, and the precise mechanism underlying it has not yet been fully elucidated. Here, we provide an integrated view of the acquired findings on the connections between trogocytosis and the immune system.